Mid-shaft clavicle fractures-factors influencing the clinical outcome after plate osteosynthesis - Narayanan, A. R.; Ponnappan, L. (International Journal of Research in Orthopaedics, 2022)
Background: Clavicle fractures constitute 5-10% of all fractures with. These fracture result from accidental fall, sports injuries or road traffic accidents The location and fracture pattern are important as it decides treatment and outcome. Our study is aimed to assess the various factors like: fracture pattern, type of implant used, and plate positioning and assessing their influence on clinical outcome. Methods: It was a prospective case-study. The study was done in department of orthopaedics, Government Villupuram Medical College Hospital Villupuram between December 2017 and December 2019. Those patients in whom there was indication for surgical management, and who were willing for surgery were admitted. Plate osteosynthesis was done using anatomical locking plate, recon plate, tubular plate. Post operative rehabilitation done. Functional and radiological assessment done at regular interval till fracture union. Results: All 32 patients had good union. Mean interval for fracture union was 4 months. 2 cases had implant failure, for which implant exit was done without any complication. Conclusions: Anatomical locking plate prove to be the ideal implant for management of mid shaft clavicle fracture. Failure by mechanical mode can be prevented by using lag screws and avoiding fracture spanning. Biological mode of failure can be prevented by guarded post operative rehabilitation in comminuted fractures.